(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2020)
Delhi, India’s state capital, has a reputation for being one of the world’s most densely populated cities. As a consequence of their findings in 2014, the World Health Organization (WHO) released this. 2014, Bandyopadhyay et al., Bandyopadhyay et al., Bandyopadhya It is unquestionably a concern for India’s future generations. We are aware of the detrimental impacts of environmental pollutants and poisons on human and other living things’ health as well as the ecosystem. Children and the elderly are the people who are most vulnerable to the pollutants’ negative effects. To prevent environment pollution in India’s major cities, a number of critical initiatives should be taken, as well as certain strict restrictions. In India, deadly diseases such as cancer are on the rise. Pollution is undoubtedly to blame for the rise in disease rates. Air pollution occurs when vapours, tiny particles, smoke, or odors are emitted into the air in a manner that is harmful to people, animals, and plants. Air pollution endangers the well-being of the individuals as well as all other living creatures on our globe.